Effects of temperature in reactive distillation of vapor from catalytic pentaerythritol tetradodecanoate (petd) reactor - Riduan, Abd. Ghani (2006)
Pentaerythritol-tetradodecanoate (PETD) was used as an essential varnish additive in magnetic wire production, It recently been conducted in many foreign countries, but in Malaysia it’s still not yet localized by any local company. The objective of this research is to study effects of temperature in catalytic PETD reactor. Method was applied by using reactive distillation as the main unit operation involving the mixture of lauric acid and pentaerythritol substrates occurred at the range 180°C to 230°C. The product from the experiment is analyzed with Gas Chromatography (GC). The result from analysis shows that the optimum temperature is at 200°C. From observation, 200°C is an optimum temperature, where it is suitable to obtain maximum reaction and higher production of PETD. From GC analysis also shows that high production of PETD when catalyst was used if compare to experiment without catalyst. Outcome from this research can be considered as pioneer process in localizing the technology, scale up and commercialization of PETD production especially in Malaysia